Ludwig Lachmann: A subjectivist institutionalist, but not a nihilist - Turowski, Krzysztof (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The legacy of Ludwig Lachmann within the Austrian School of Economics is subject to several interpretations in the literature: though he clearly considered himself a member of the school and he influenced many Austrian economists, his particular methodological claims prompted Murray Rothbard to disavow him as a nihilist. In this article, we defend Lachmann by arguing that in order to defend his methodological stance he invoked extra-Austrian influences (Max Weber, G.L.S. Shackle). This way, he championed subjectivist institutionalism consistently both in theory and in practice. His approach leaves a peculiar, unorthodox, yet positive legacy for contemporary Austrian economics, not so far from the orthodox Misesian stance as it is broadly understood.